2022
DOI: 10.1242/dev.199997
|View full text |Cite
|
Sign up to set email alerts
|

Aster repulsion drives short-ranged ordering in the Drosophila syncytial blastoderm

Abstract: Biological systems are highly complex, yet notably ordered structures can emerge. During syncytial stage development of the Drosophila melanogaster embryo, nuclei synchronously divide for nine cycles within a single cell, after which most of the nuclei reach the cell cortex. The arrival of nuclei to the cortex occurs with remarkable positional order, which is important for subsequent cellularisation and morphological transformations. Yet, the mechanical principles underlying this lattice-like positional order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 76 publications
(112 reference statements)
3
38
0
Order By: Relevance
“…Furthermore, the inefficient separation led to a lower nuclear ordering in the subsequent interphase. In our control experiments, UbcH10-arrest/release approach is able to reproduce the non-sibling internuclear distance recently reported for this division cycle (cycle 11) (de-Carvalho et al 2022). In contrast, upon ER disruption, sibling nuclear distance was shorter and the distances between non-sibling nuclei were longer when compared to the control condition (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, the inefficient separation led to a lower nuclear ordering in the subsequent interphase. In our control experiments, UbcH10-arrest/release approach is able to reproduce the non-sibling internuclear distance recently reported for this division cycle (cycle 11) (de-Carvalho et al 2022). In contrast, upon ER disruption, sibling nuclear distance was shorter and the distances between non-sibling nuclei were longer when compared to the control condition (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Our previous work has revealed that the spindle pole MTOC plays a crucial role in daughter nuclei separation and nuclear spacing in the syncytial embryo (Telley et al 2012; de-Carvalho et al 2022). Having observed spindle pole detachment upon cyATL injection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the inefficient separation led to a lower nuclear ordering in the subsequent interphase. In our control experiments, the UbcH10-arrest/release approach is able to reproduce the non-sibling internuclear distance recently reported for this division cycle (cycle 11) ( de-Carvalho et al, 2022 ). In contrast, upon ER disruption, sibling nuclear distance was shorter and the distances between non-sibling nuclei were longer when compared with the control condition ( Fig 5K and L ).…”
Section: Resultsmentioning
confidence: 82%
“…Our previous work has revealed that the spindle pole MTOC plays a crucial role in daughter nuclei separation and nuclear spacing in the syncytial embryo ( Telley et al, 2012 ; de-Carvalho et al, 2022 ). Having observed spindle pole detachment upon cyATL injection ( Fig 4 ), we next aimed to probe nuclear separation after disruption of the ER in embryos undergoing the changes characteristic of a normal mitotic exit.…”
Section: Resultsmentioning
confidence: 99%
“…The laser ablation system used in this study was described elsewhere (de-Carvalho et al, 2022). Follicle cells were ablated using circular ablation (60 px diameter, 5 px step size) and 50% laser power.…”
Section: Laser Ablationmentioning
confidence: 99%